Experimental Study of The Fan Turbine Performance in Oscillating Water Column with Airflow System in Venturi Directional as Wave Energy Converter - Madi Madi; Muhammad Gufran Nurendrawan Bangsa; Bintari Citra Kurniawan; Andi Andi; Fathan Hafiz; Putty Yunesti; Amelia Tri Widya; Asfarur Ridlwan; Daniel Epipanus (WAVE: Jurnal Ilmiah Teknologi Maritim, 2023)
The Indonesian Ocean Energy Association has ratified the potential for ocean wave energy in Indonesia with a theoretical possibility of 141.472 x 109 watts. Unfortunately, this vast potential has not yet been utilized optimally in the Indonesian seas. Ocean wave energy technology has developed rapidly in various countries worldwide. The Oscillating Water Column (OWC), which uses the oscillating movement of ocean waves' airflow, is one of the most well-known systems for generating power from waves. A novel model of ocean wave power generation was created with the use of a more basic fan turbine and inspiration from OWC. It is directly integrated with an electric dynamo and an internal flow system in a venturi tube, which can increase airspeed based on continuity theory. The experiment's results succeeded in creating up and down movements of ocean waves with a high tide of 15 cm and a low tide of 12 cm. Ocean wave oscillations can produce gusts of air with a speed of 1.56 m/s. The final result is obtained by model performance with an average turbine rotation speed of 42.191 rpm, an average electric voltage of 0.809 volts, and a more optimal turbine efficiency of 67.9%.